Evaluation of alternatives to replace or reduce viticulture conventional fungicides: Eucalyptus globulus essential oil and aqueous extract - Fernandes, Beatriz; Duarte, Rute; Paiva, Cristiana; Oliveira-Pacheco, João; Cachada, Anabela; Pereira, Ruth (Frontiers in Environmental Science, 2025)
The use of plant protection products is often related to environmental contamination, including copper-based products as the Bordeaux Mixture (BM) and synthetic fungicides like folpet (active substance), both of which face use restriction from the European Union due to their toxicity. As alternatives, plant-based products such as E. globulus extracts (EE) or essential oils (EO) are considered more sustainable and environmentally friendly products with known biocidal properties, but their impacts on non-target species remain poorly known. These products might be effective not only on existing pathogenic species that infect grapevines, but also on other potential pathogens, emerging in a context of climate change. This study aimed to evaluate the fungicidal effects of E. globulus EE and EO, alone or in combination with BM and folpet through growth inhibition assays using target (Botrytis cinerea), potentially target (Chaetomium elatum) and non-target (Lentinus sajor caju and Phanerochaete chrysosporium) fungal species, under in vitro conditions. Different exposure methods were also assessed. Results showed that EE alone inhibited the growth of the fungi species, though sensitivity varied with the application methods. The combination of EE with BM was only effective when incorporated into the growth medium, becoming a promising alternative to reduce BM use, however, the same cannot be said for the mixture of EE and folpet. E. globulus EO effectively inhibited the target fungi growth, still, the non-target species were also affected, highlighting that a careful evaluation of plant-based products is of utmost importance, considering the effects that they have on non-target organisms of the ecosystem.